Amplified spontaneous emission and optical gain spectra from stilbenoid and phenylene vinylene derivative model compounds - BLAU, WERNER (My University, 1999)
We report single-pass optical gain measurement in polystyrene! waveguides doped with stilbenoid and phenylene vinylene derivative model compounds under picosecond excitation. Using a wavelength dependent model of amplified spontaneous emission, we produce optical gain spectra for these materials. Net optical gains of g 5 15? 20 cm 2 1 are deduced. The spectra also exhibit features consistent with excited state absorption and fluorescence depletion via stimulated emission. A figure of merit describing the potential of a material for use as a laser medium is presented and comparisons with other recent publications are made. This comparison indicates that organic materials can compete with inorganic semiconductors for optically pumped applications.
PUBLISHED
Keywords: single-pass optical gain measurement in polystyrene; single-pass optical gain measurement in polystyrene